Postavení Policie ČR v systému krizového řízení - Bednářová, Zdeňka (Vysoké učení technické v Brně. Fakulta chemická, 2010)
Tato bakalářská práce, která je rozdělena na dvě části – teoretickou a praktickou, objasňuje zapojení Policie ČR do systému krizového řízení našeho státu. Teoretická část je věnována problematice krizového řízení, integrovanému záchrannému systému a úkolům plněným Policií ČR v jejich rámci, a to včetně mechanismů sloužících k zabezpečení krizové připravenosti u tohoto bezpečnostního sboru. Praktická část blíže popisuje činnost a organizaci konkrétního oddělení krizového řízení Policie ČR. Analýza činnosti oddělení je východiskem pro závěrečné hodnocení přínosu krizových pracovišť Policie ČR pro praktický výkon služby.

This bachelor paper which is divided into two parts – theoretical and practical - brings out involvement of Police of the Czech Republic into the system of our state´s crisis management. Theoretical part is turned to the questions of crisis management, joint rescue system and to the tasks subserved within this system by Police of the Czech Republic, namely with inclusion of gadgetry serving for securing of this security organization´s crisis preparedness. Practical part more closely describes working and organizational structure of concrete police crisis management departement. Analysis of this departement´s working subserves as the base for concluding valuation of police crisis departements´ contribution to functional service.
Role of the Police of the Czech Republic in the System of Crisis Management
Keywords: Policie České republiky; pracoviště krizového řízení Policie České republiky; krizové řízení; integrovaný záchranný systém; mimořádná událost; krizová situace.; Police of the Czech Republic; departement of crisis management of Police of the Czech Republic; crisis management; joint rescue system; extraordinary incident; crisis situation.